Identification and Cluster Analysis of Pitcher Plant (Nepenthes spp.) from South Sumatera Indonesia - Weni Lestari; Jumari Jumari; Rejeki Siti Ferniah (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Nepenthes spp. is a typical plant of Southeast Asia especially Indonesia which has a special leaf modification called a pitcher. The largest number of Nepenthes spp. species in Indonesia is on the island of Sumatra. The purpose of this reseach was to identify and analyze cluster Nepenthes spp. from South Sumatra based on morphological characteristics. The specimens were collected from the forest of Tekorejo Village, Air Itam Village and cultivation location in Palembang city of South Sumatra. Identification of morphological characters performed on the characteristics of root, stem, leaves, and pitcher. The morphological data is used for cluster analysis using NTSYS software version 2.02. The identification results showed 9 variants of Nepenthes spp. which belong to the species N. mirabilis, N. gracilis, and N. sumatrana. Dendogram analysis results form two main clusters with a similarity value of 22%. The first cluster consists of N. mirabilis and N. sumatrana. The second cluster consists of N. gracilis. Based on the results of this study can be concluded that the species Nepenthes spp. South Sumatra is N. mirabilis, N. gracilis, and N. sumatrana. The results of this study will be dedicated to updating information about the existence of Nepenthes spp. from South Sumatra and his cluster.